Mastitis management-effective methods to reduce somatic cell counts - John F. Smith; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2000)
Mastitis is the most costly health concern in the dairy industry today. Annual losses have been estimated at 180 to 185 per cow. Based on this figure, annual losses for Kansas producers may exceed 15 million. Nationally, mastitis may cost the industry 1.8 billion annually. Although treatment and premature culling for clinical mastitis are costly, about two-thirds of the cost is associated with reduced milk production caused by subclinical mastitis. Effective mastitis control programs are necessary for the dairy industry today. Prevention of subclinical mastitis is the key to lowering the somatic cell counts (SCC). Elevated bulk tank SCC (>250,000/ml) are an indication that a significant number of the cattle are infected with mastitis-causing bacteria and corrective action is required. Key areas to evaluate are cow housing, milking equipment, and milking procedures. Utilization of milk culture data is necessary to determine if elevated SCC are due to environmental or contagious organisms. In addition, cultures of milk samples from individual cows may be needed to identify cattle infected with contagious organisms. Correction of deficiencies in housing, milking procedures, and milking equipment will effectively control environmental mastitis. Identification, segregation, and future culling of animals infected with contagious organisms are necessary for control of contagious mastitis. An effective monitoring system that includes individual-cow SCC, individual-cow bacterial cultures, and bulktank bacterial cultures will ensure a low bulk-tank SCC and a low level of mastitis. It is a health issue that requires constant attention, because success is achieved with attention to detail on the dairy as a whole, and lack of attention in only one segment of the dairy may result in significant increases in mastitis. Success of the program requires that all employees and the management team (managers, herdsmen, veterinarians, nutritionists, milking equipment technicians, and consultants) emphasize increasing milk quality by controlling mastitis.; Dairy Day, 2000, Kansas State University, Manhattan, KS, 2000;
Keywords: Dairy Day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-166-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 861; Dairy; Mastitis; Milk quality; Bacteria; Milk production